KONSEPSI (KESALAHPAHAMAN) BIMBINGAN DAN KONSELING DALAM PENDIDIKAN - Nurfarida Deliani (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Guidance and counseling is import commodity, where, the outgrowth still transient. Till now, There is no solid agreement or misconception between guidance and counseling expert for implementation of guidance and counseling in Indonesia. Those problems could be appear due to the lack of competency or knowledge of the counselor in Indonesia. This misconception must be eliminated for the better serve of guidance and counseling in Indonesia. This article aim to share and giving about what is the guidance and counseling, and position of guidance and counseling in school or community.